Determinantes of AFP demand in Chile: New empirical evidence from individual data - Berstein, Solange (Estudios de Economía, 2016)
This article is the first one to use individual data to analyze the demand forAFP in Chile. This study implements panel data techniques which allow us toestimate the switch probability of an AFP customer. Results confirm the fundamentalrole of sales agents, which was already suggested by previous studiesthat have used aggregated data by AFP. Particularly, we show that althoughprice and return elasticity of demand are low, it raises notably when associatedto a sales agent visit.